Why Science Communication, and Does It Work? A Taxonomy of Science Communication Aims and a Survey of the Empirical Evidence - Kappel, Klemens; Holmen, Sebastian Jon (Frontiers in Communication, 2019)
In this paper, we offer a novel conceptual framework of the most important aims for science communication efforts found in the contemporary literature on science communication. We identify several distinct aims present in the literature such as generating public epistemic and moral trust, generating social acceptance, and enhancing democratic legitimacy, and we discuss some of the relations between the different aims. Finally, we examine whether and, if so, to what extent these different aims can be said to have been successfully reached in practice and find that the empirical literature regarding the evaluation of science communications efforts is scarce. We conclude by suggesting that science communicators be attentive to formulating their communicative aim(s) in more precise terms, as well as conduct systematic studies of the effectiveness of their communicative efforts.